STABILITY AND STABILIZATION OF NONLINEAR DYNAMICAL SYSTEMS - Sattayatham, P.; Saelim, R.; Sujitjorn, S. (ASEAN Journal on Science and Technology for Development, 2003)
Exponential and asymptotic stability for a class of nonlinear dynamical systems with uncertainties is investigated.  Based on the stability of the nominal system, a class of bounded continuous feedback controllers is constructed.  By such a class of controllers, the results guarantee exponential and asymptotic stability of uncertain nonlinear dynamical system.  A numerical example is also given to demonstrate the use of the main result.